Sistema modular para el laboratorío de microcontroladores de la ESPOL - Valdivieso Armendáriz, Carlos (2009)
This thesis corresponds to the creation of a Modular System to facilitate microcontroller’s teaching within the scope of laboratory practices. For this reason, a study of the present market reality was made, analyzing the most efficient way to benefit students at ESPOL and extend it to all the students in Ecuador. It was possible to visualize a modular educational system based in our reality as a country and as an educational institution, that allows us, the formation and development of skills and habits, derived from the teaching process, in the students that take microcontrollers as a subject, contributing with great benefit to their future careers.